Effects of low temperature on flowering and the expression of related genes in Loropetalum chinense var. rubrum - Zhang, Damao; Chen, Qianru; Zhang, Xia; Lin, Ling; Cai, Ming; Cai, Wenqi; Liu, Yang; Xiang, Lili; Sun, Ming; Yu, Xiaoying; Li, Yanlin (Frontiers in Plant Science, 2022)
Introduction Loropetalum chinense var. rubrum blooms 2-3 times a year, among which the autumn flowering period has great potential for exploitation, but the number of flowers in the autumn flowering period is much smaller than that in the spring flowering period. Methods Using ‘Hei Zhenzhu’ and ‘Xiangnong Xiangyun’ as experimental materials, the winter growth environment of L. chinense var. rubrum in Changsha, Hunan Province was simulated by setting a low temperature of 6-10°C in an artificial climate chamber to investigate the effect of winter low temperature on the flowering traits and related gene expression of L. chinense var. rubrum. Results The results showed that after 45 days of low temperature culture and a subsequent period of 25°C greenhouse culture, flower buds and flowers started to appear on days 24 and 33 of 25°C greenhouse culture for ‘Hei Zhenzhu’, and flower buds and flowers started to appear on days 21 and 33 of 25°C greenhouse culture for ‘Xiangnong Xiangyun’. The absolute growth rate of buds showed a ‘Up-Down’ pattern during the 7-28 days of low temperature culture; the chlorophyll fluorescence decay rate (Rfd) of both materials showed a ‘Down-Up-Down’ pattern during this period. The non-photochemical quenching coefficient (NPQ) showed the same trend as Rfd, and the photochemical quenching coefficient (QP) fluctuated above and below 0.05. The expression of AP1 and FT similar genes of L. chinense var. rubrum gradually increased after the beginning of low temperature culture, reaching the highest expression on day 14 and day 28, respectively, and the expression of both in the experimental group was higher than that in the control group. The expressions of FLC, SVP and TFL1 similar genes all decreased gradually with low temperature culture, among which the expressions of FLC similar genes and TFL1 similar genes in the experimental group were extremely significantly lower than those in the control group; in the experimental group, the expressions of GA3 similar genes were all extremely significantly higher than those in the control group, and the expressions all increased with the increase of low temperature culture time. Discussion We found that the high expression of gibberellin genes may play an important role in the process of low temperature promotion of L. chinense var. rubrum flowering, and in the future, it may be possible to regulate L. chinense var. rubrum flowering by simply spraying exogenous gibberellin instead of the promotion effect of low temperature.